Endoscopic survey of esophageal cancer in a high-risk area of China - Lu, Xu-Jing (World J Gastroenterol, 2004)
AIM: To characterize the histological types of esophageal and cardiac mucosa by endoscopic survey of a population in a high-risk area of esophageal cancer of China. METHODS: A selected cohort of residents in Cixian County during December 2001 and May 2002 was surveyed by using Lugol’s staining, followed by computer-based statistical analysis of the data with SPSS 10.0 software. RESULTS: Histologically, the detection rates of squamous epithelial acanthosis, squamous epithelial atrophy, and basal cell hyperplasia in the esophagus were 1.9% (38/2013), 0.1% (3/2013) and 0.9% (18/2013) respectively, and those of mild, moderate, and severe esophagitis were 34.9% (703/2013), 1.6% (33/2013) and 0.2% (2/2013) respectively. Mild, moderate, and severe esophageal dysplasia were detected in 8.6% (172/2013), 7.8% (157/2013) and 2.6% (53/2013) respectively in the selected population, whereas in situ carcinoma, intramucosal carcinoma, invasive squamous carcinoma of the esophagus in 2.5% (50/2013), 0.2% (4/2013) and 0.7% (14/2013) respectively. The detection rates of non-atrophic gastritis and atrophic gastritis of the cardia were 36.3% (730/2013) and 11.5% (232/2013) respectively, with mild and severe dysplasia of the cardia detected in 2.5% (51/2013) and 0.8% (17/2013), respectively, in this population; the rates of intramucosal adenocarcinoma and invasive adenocarcinoma of the cardia were 0.1% (3/2013) and 0.8% (17/2013) respectively. The detection rate of esophageal cancer at early stage was 79.4% (54/68). The survey rate (ratio of examined population to expected population) was 73.8% (2013/2725). CONCLUSION: Histologic types of the esophageal and cardiac mucosa were characterized by endoscopic survey in a high-risk population of esophageal cancer, which may help the early detection and treatment of esophageal and cardiac cancers and dysplasia, and reduce the mortality of such malignancies.